2021
DOI: 10.1016/j.isci.2021.102420
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type-resolved quantitative proteomics map of interferon response against SARS-CoV-2

Abstract: The commonly used laboratory cell lines are the first line of experimental models to study the pathogenicity and performing antiviral assays for emerging viruses. Here, we assessed the tropism and cytopathogenicity of the first Swedish isolate of SARS-CoV-2 in six different human cell lines, compared their growth characteristics and performed quantitative proteomics for the susceptible cell lines. Overall, Calu-3, Caco2, Huh7, and 293FT cell lines showed a high to moderate level of susceptibility to SARS-CoV-2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 41 publications
6
74
0
Order By: Relevance
“…This indicates that IFIT1 might be an important antiviral-factor that needs further attention. Also, the differences observed among the two cell lines underscores the drawback of studying a single cell line (Huh7 in this case) as it may not be reflective of other cell populations where there could be differential regulation of IFN-response 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that IFIT1 might be an important antiviral-factor that needs further attention. Also, the differences observed among the two cell lines underscores the drawback of studying a single cell line (Huh7 in this case) as it may not be reflective of other cell populations where there could be differential regulation of IFN-response 44 .…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of our study is that the analysis is restricted to only one cell line that may not provide a comprehensive picture since we have observed cell-type specific differences in susceptibility to SARS-CoV-2 and interferon response 44 . Furthermore, Huh7 is an immortalized cancer cell line, which may not be physiologically representative of the human tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This cell line showed limited endogenous ACE2 expression level and was non-permissive to SARS-CoV-2 infection under submerged culture conditions ( Fig. 1 F–H) [ 7 ]. Our study and other studies demonstrated that exogenous expression of human ACE2 mediates SARS-CoV-2 entry and renders A549 cells permissive for SARS-CoV-2 infection [ [24] , [25] , [26] ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the interaction between ACE2 and S protein has attracted attention, because emerging SARS-CoV-2 variants possess amino acid substitutions in the receptor binding domain of S protein which can increase the binding affinity to human ACE2 [ 5 ]. In addition, the exogenous expression of ACE2 confers SARS-CoV-2 susceptibility to cells which are normally resistant to infection [ 6 , 7 ]; therefore, ACE2 is a major determinant of SARS-CoV-2 susceptibility. On the other hand, certain host proteases proteolytically activate (or prime) S protein for membrane fusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation